The Effect of Some Parameters in the Blood on Reproductive Efficiency in Dairy Cows During Insemination - Aydın, Hanifi (Progress in Nutrition, 2021)
Study Objectives: Infertility is one of the common factors that negatively affect productivity and quality in dairy farms. The study aimed to determine the levels of nitric oxide, total protein, glucose, vitamin C, cholesterol, urea nitrogen, MDA, and carotene during insemination and the relationship between these values and fertility. For this purpose, a total of 80 Holstein cows were studied. Methods: Non-pregnant cows whose pregnancies were diagnosed by rectal examination were separated for the study and synchronization was applied. Blood samples were taken from the vena jugularis at the same time 12 hours after insemination and sent for analysis. After the cows were detected by ultrasound on the 30th day, the relationship between the blood values ​​of the pregnant and non-pregnant cows with the pregnancy rate was investigated. Results: Pregnancy rates were determined as (70%) as a result of the research. When the comparison of biochemical parameters obtained from the study according to pregnancy status was examined, it was seen that there was no statistically significant difference in all other data except for glucose level (69.53 mg /dl pregnant, 153.12 mg /dl not pregnant). Conclusion: Infertility rate (30%) has been associated with MDA (7.92 mmol / L in pregnant cows, 9.00 mmol / L in non-pregnant cows), an indicator of oxidative stress in addition to β-carotene (71.26 μg / dl in pregnant, and 93.54 μg /dl in nonpregnant) deficiency, high glucose, and BUN (pregnant 21.56 mg /dl, non-pregnant 22.63 mg /dl) levels.